Essays on socioeconomic shocks and policies in agriculture - Iglesias Pinedo, Wilman Javier (2021)
The three chapters of this dissertation examine the effects of a series of external shocks and policies on the value of production, productivity, and crop supply in agriculture. Using unique panel data sets for Colombia and the United States combined with production economics models, this dissertation provides new estimates and perspectives on agricultural sector response to socio-economic phenomena and some policies in interrelated markets. Chapter 1 uses a production function that includes violence and forced intra-national displacement of the rural population during 1995-2017. This chapter estimates the effect of armed conflict on the productivity of Colombian agriculture. Although the agricultural sector has traditionally been crucial to the Colombian economy, the annual growth rate of the value of agricultural production has fluctuated significantly over the last two decades, with a relatively low growth rate since 1990. Therefore, it is of particular interest to understand how violence and the internal displacement of people have affected the use of resources and productivity in Colombian agriculture. Chapter 2 investigates the effect of anti-drug policies (coca eradication campaigns and interdiction of cocaine processing laboratories) implemented under Plan Colombia (a joint U.S.-Colombia policy aimed at curbing the supply of illicit drugs) on the value of agricultural production of regions in Colombia with coca crops. The difference- in-difference analysis in this chapter allows evaluating the impact of the anti-drug strategy implemented by the Colombian government since 2007 on the agriculture GDP in the coca- growing regions. Chapter 3 examines the effects of a policy in the ethanol market on the supply of biomass from corn at the extensive and intensive margins. A profit function framework and simultaneous equations panel model are adopted to analyze the land allocation and crop yield responses using the U.S 2007’s Renewable Fuel Standard (RFS) that mandated specified quantities of total biofuels. The RFS is assumed to create exogenous market shocks to the supply of corn biomass in several counties along the Great Plains of the U.S. It is of particular interest to assess how much the supply of corn biomass to (potentially) produce fuels has structurally changed because of the mandates. Keywords: Productivity. Panel Data. Agriculture. Conflict. Antidrug Policy. Energy Policy.